The introduction of disincentives for early retirement and its effect on labor market participation - Daniel Kemptner; Boenke Timm; Luethen Holger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We evaluate the actual effectiveness of disincentives that have been introduced for early retirement in Germany. Therefore, we set up a detailed model of the German social security and tax system with special attention to the PAYG-pension system. Building on the fact that the institutional changes were phased in, impacting birth cohorts to a different degree we are able to estimate the parameters of a structural dynamic retirement model. This allows us to answers the question, whether and to what degree disincentives are able to steer retirement behavior of German pensioners. These estimates are based on high quality administrative data. We also discuss the implications for the financial stability of the PAYG-pension scheme and investigate distributional effects. On the basis of our simulations we try to give some insights on how a complementary private old age insurance plan (e.g. a life annuity) would have to look like, if the pre-reform level of old age income is to be retained.
Keywords: C61; J26; H55; 330